Enhancing Tourism Accessibility for the Deaf and Hard-of-Hearing with XR Technology: A Systematic Literature Review - Mohd Harith Syazwan, Samsawi; Suriati Khartini, Jali; Mohamad Imran, Bandan; Syahrul Nizam, Junaini; Sylvester, Arnab; Phei Chin, Lim; Kuryati, Kipli; Sarni Suhaila, Rahim (2025)
In recent years, Extended Reality (XR) technology has become more and more prevalent in all facets of life. It can be applied to enhance deaf and hard-of-hearing accessibility in tourism environments. The goals of this review are to determine the challenges to accessibility that the hard-of-hearing and deaf community must overcome, the usefulness of such technology to this group, and the degree to which it can improve accessibility for this population when travelling. 16 papers have been assessed based on the keyword search of the Scopus and Web of Science databases. The methodologies, difficulties, and advantages of XR technology in tourism for the hard-of-hearing are assessed in relation to these studies. Lastly, a number of areas where the existing methods could be improved upon are identified, and recommendations are made for additional research.